2022
DOI: 10.1021/acsanm.2c02722
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Controllable Optical Absorptions and Magneto-Optical Properties of Magnetic CrI3 Nanoribbons: Implications for Compact 2D Magnetic Devices

Abstract: A chromium triiodide (CrI3) monolayer has an interesting ferromagnetic ground state. In this work, we calculate band structures and magnetic moments of tensile-strained and bent zigzag CrI3 nanoribbons with density functional theory. The edge iodine atoms form flat low-lying conduction bands and couple with chromium atoms ferromagnetically, while the non-edge iodine atoms weakly couple antiferromagnetically. Narrow CrI3 nanoribbons have two locally stable magnetic moment orientations, namely, out-of-plane and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the medical field, nanoribbons offer potential for controlled drug delivery and improvements in magnetic imaging . In magnetic catalysis, they can act as catalysts, facilitating specific chemical reactions, and display capability in the fabrication of advanced magnetic sensors. , In magnetic information storage, the improved properties of nanoribbons contribute to more efficient systems . In addition, they have significant potential in spin electronics, promoting advances in spintronics devices .…”
Section: Introductionmentioning
confidence: 99%
“…In the medical field, nanoribbons offer potential for controlled drug delivery and improvements in magnetic imaging . In magnetic catalysis, they can act as catalysts, facilitating specific chemical reactions, and display capability in the fabrication of advanced magnetic sensors. , In magnetic information storage, the improved properties of nanoribbons contribute to more efficient systems . In addition, they have significant potential in spin electronics, promoting advances in spintronics devices .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoribbons are interesting, reduced forms of 2D layered materials. [18][19][20][21][22][23][24][25][26] Compared with their 2D counterparts, they have more spatial confinement effects and rich edge states, making Department of Physics, Temple University, Philadelphia, PA 19122, USA. E-mail: hongtang@temple.edu † Electronic supplementary information (ESI) available: Technical note 1 for spinpolarization anisotropy analyses for A12WSe 2 and A7WSe 2 nanoribbons, note 2 for the d-orbital decomposition analyses for A13WSe 2 , Table S1 for the five observations to the band structure map of the d-orbital decomposition of the spin-polarization along the x and y axes for the A13WSe 2 nanoribbon under different bending conditions, note 3 for the k-grid convergence test of the optical absorption spectrum, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…20 The carbon atoms in each edge of graphene zigzag nanoribbons (GZNRs) are ferromagnetically coupled, while the inter-edge coupling changes from antiferromagnetic in narrow semiconductive GZNRs to ferromagnetic in wide metallic GZNRs. 19 Tang et al 21 showed that the direction of magnetization in CrI 3 nanoribbons can be stably aligned both out-of-plane and parallel to the ribbon axis, increasing their operating controllability. Also, the rich exciton states are shown in SiC, 22 MoS 2 , 23 black phosphorene, 24 and CrI 3 nanoribbons, 21 and the exciton states can be tuned by bending or strains in the nanoribbons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations